Sustainability of Open Educational Resources in Forensic Sciences: International Experience - Palkova, Karina; Agapova, Olena; Zīle, Aelita; Polianskyi, Anton; Vadym, Khosha; Hasparian, Serafyma; Mykhailo, Mozhaiev (European Journal of Sustainable Development, 2022)
Open educational resources are among the important factors that affect the quality of contemporary education. The new form of education has been recognised by UNESCO and has become an important element in reaching sustainable development goals in educational sector. This article covers the experience of using open educational resources for expert support in justice, based on international experience. To identify the possibility of using open educational resources in the specific area of forensic experts’ education, the authors of the article have conducted a survey among expert community, and the survey results are presented in this study. Representatives of expert institutions from Bosnia-Herzegovina, Bulgaria, Czech Republic, Georgia, Germany, Greece, Israel, Latvia, Montenegro, Poland, Slovenia, Ukraine and other countries have participated in the survey. The analysis of survey results shows that the introduction of open educational resources is acceptable for most respondents. It was found that ‘OER: Forensic Science’ project is going to be the first educational content of the kind to be introduced in forensic expert institutions and universities entitled to support educational activities. It is proven that open educational resources can enhance quality of the learning process at two levels at least. First, it is the quality of teaching and secondly, it is the new digital approach to learning environment that allows access to all studies necessary to perform forensic expert activities.